2017
DOI: 10.1001/jamaoto.2017.1454
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Alkaline Water and Mediterranean Diet vs Proton Pump Inhibition for Treatment of Laryngopharyngeal Reflux

Abstract: Our data suggest that the effect of PPI on the RSI based on proportion reaching a 6-point reduction in RSI is not significantly better than that of alkaline water, a plant-based, Mediterranean-style diet, and standard reflux precautions, although the difference in the 2 treatments could be clinically meaningful in favor of the dietary approach. The percent reduction in RSI was significantly greater with the dietary approach. Because the relationship between percent change and response to treatment has not been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
82
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(88 citation statements)
references
References 58 publications
(91 reference statements)
3
82
0
3
Order By: Relevance
“…Theoretically, this approach could decrease stimulation of the various chemo‐ and mechanoreceptors and thus diminish the peripheral stimulation. To theoretically address potential upregulated acid and chemoreceptors, we used an approach of treating LPR using a diet‐based approach that we previously demonstrated to be as efficacious if not more so in controlling laryngopharyngeal symptoms avoiding the use of proton pump inhibitor with their suggested potential side effects and costs . In addition, this diet‐based approach affords the improved health benefits of decreased heart disease, diabetes, stroke, and many cancers, highlighting the need for physician education to improve overall improvement in chronic disease outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Theoretically, this approach could decrease stimulation of the various chemo‐ and mechanoreceptors and thus diminish the peripheral stimulation. To theoretically address potential upregulated acid and chemoreceptors, we used an approach of treating LPR using a diet‐based approach that we previously demonstrated to be as efficacious if not more so in controlling laryngopharyngeal symptoms avoiding the use of proton pump inhibitor with their suggested potential side effects and costs . In addition, this diet‐based approach affords the improved health benefits of decreased heart disease, diabetes, stroke, and many cancers, highlighting the need for physician education to improve overall improvement in chronic disease outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…A six‐point or greater reduction in the RSI score is considered a clinical responder . We have previously reported that standard reflux precautions, a Mediterranean diet, and alkaline water had resulted in a clinically significant six‐point reduction in the RSI score in 63% of patients . Using this criterion, patients were grouped as responders or nonresponders, and statistical significance was determined using the Fisher exact test with a placebo effect of 25%.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…LPR may even lead to carcinoma of the larynx. The LPR is considered to be mainly mediated through a process of exposure of the laryngopharynx to an acid environment in the presence of pepsin (7). The definition of LPR is extraoesophageal variant of gastroesophageal reflux disease, that affects the larynx and pharynx (8).…”
Section: Introductionmentioning
confidence: 99%
“…1 To date, a very few number of studies interested to the impact of diet and lifestyle modifications on the improvement of symptoms, signs and voice quality in LPR disease. [5][6][7] However, with regard to the significant risk of adverse effects and the increasing cost of long-term PPI prescription, 5,6,8 diet and lifestyle modifications remain an interesting way for short and long-term control of LPR, especially in patients with chronic course.…”
mentioning
confidence: 99%